PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE SOMATIC, AUDITORY, VISUAL, INTELLECTUAL (SAVI) TERHADAP KEMAMPUAN MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA KELAS X SMAN 5 PEKANBARU - Rosa Satya Negara M, Adinda; Charlina; Sinaga, Mangatur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the difficulties faced by tenth-grade students at SMAN 5 Pekanbaru in writing report texts of observation results, specifically regarding text structure, linguistic features, and low writing interest. The objective of this study was to determine the influence of the Somatic, Auditory, Visual, Intellectual (SAVI) cooperative learning model on students' ability to write observation report texts. This research employed a quasi-experimental method with a non-equivalent control group design. The population consisted of all tenth-grade students at SMAN 5 Pekanbaru, with class X-7 as the experimental group and class X-6 as the control group. Data were collected through pretest and posttest writing assignments and analyzed using descriptive statistics, Mann-Whitney U test, and simple linear regression via SPSS 26. The results showed a significant difference in writing abilities between the two groups. The experimental group achieved a higher mean score of 82.00 compared to the control group’s 67.60. Hypothesis testing through the Mann-Whitney U test yielded a significance value of 0.000 (< 0.05), and the regression test confirmed that the SAVI model significantly influenced students' writing skills. In conclusion, the application of the SAVI cooperative learning model effectively enhances the ability of tenth-grade students at SMAN 5 Pekanbaru to write report texts of observation results by engaging multiple learning modalities.